Fields in middle school energy instruction to support continued learning of energy - Kristin Fiedler; Marcus Kubsch; Knut Neumann; Jeffrey Nordine (Physical Review Physics Education Research, 2023)
Science education research has repeatedly revealed students’ problems with understanding the energy concept, in particular, their understanding of potential energy. Newer research suggests that teaching students fields as a means to store potential energy may promote a more consistent understanding of the energy concept. Yet, it is presently unknown if the helpfulness of fields is limited to particular manifestations of potential energy or if the conceptualization of potential energy as energy stored in fields may constitute a coherent approach that supports students’ continued learning on energy. To address this issue, we carried out a quasiexperimental pre-post-test study with N=64 students from grade 6, with students being assigned to one of two conditions (fields-based vs nonfields-based approach to energy instruction). We also compared students continued learning in a subsequent unit on electric energy. Our findings suggest that students in the fields approach not only outperformed students in the nonfields approach, they were, in particular, able to use their understanding of potential energy to make better sense of electric energy, a form of energy previously unknown to them. The results of our study imply that fields can help students develop a deeper understanding of energy, in particular potential energy, and support continued learning about energy; that is, the learning about additional forms of energy.